The Social Networks of Homeless Youth Experiencing Intimate Partner Violence. (August 2014) - Petering, Robin; Rice, Eric; Rhoades, Harmony; Winetrobe, Hailey
While there is a growing body of research on intimate partner violence (IPV) experienced by the housed youth population, a limited amount is known about IPV experienced by homeless youth. To our knowledge, no previous studies have examined how homeless youths' experience of IPV is related to their social network, even though the social networks of homeless youth have been shown to be significant indicators of health and mental health. The purpose of this study is to understand the relationship between IPV, gender, and social networks among a sample of 386 homeless youth in Los Angeles, California. Results revealed that one fifth of the sample experienced IPV in the past year. Stratified regression models revealed that IPV was not significantly related to any measure of male social networks; however, females who experienced IPV had more male friends (β = 2.03, SE = 0.89, p < .05) than females who did not experience IPV. Female homeless youth who witnessed family violence during childhood had more male friends (β = 2.75, SE = 1.08, p < .05), but those who experienced sexual abuse during childhood had fewer male friends (β = −2.04, SE = 0.93, p < .05). Although there was no significant difference in the rate of IPV victimization across genders, the context of this abuse appears to be drastically different. The results suggest that females with more male friendships are at greater risk for exposure to IPV. To date, there are few effective youth-targeted IPV prevention programs and none have been shown to be effective with homeless youth. These results provide insight into future program development.